PENGARUH LATIHAN METODE MODIFIED TWO ON ONE DENGAN METODE RHYTHM DRILL TERHADAP KEMAMPUAN BACKHAND DRIVE TENIS - Mulyono, Slamet Hendri; Soedjatmiko, Soedjatmiko (Universitas Negeri Semarang, 2016)
Problem: Is there any influence of exercise backhand drive groundstrokes with Modified method Two On One and methods Rhythm Drill on the ability backhand groundstrokes drive? Which drive backhand groundstrokes exercise is better between method Modified Two On One with Rhythm Drill on the ability backhand groundstrokes drive?This type of quantitative research with the experimental method. The research sample Club men's tennis player Phapros 2016 amounted to 10 people. The sampling technique used purposive sampling technique. data analysis using paried sample t test using SPSS version 16.Research outputs obtained: 1) The value t, -3965, 0.017 significance value of <0.05 and t value 3.000, 0.040 significance value <0.05 then there are differences in the effects of exercise backhand drive groundstrokes with Modified method Two On One and methods Rhythm Drill on the ability backhand drive groundstrokes in tennis club Phapros Semarang 2016; 2) the mean of the experimental group of 22,800 is greater than the control group mean of 18,700, exercise training methods backhand groundstrokes drive two on one groundstrokes better than Rhythm Drill training methods on the ability of tennis on a tennis backhand drive Clubs son Phapros Semarang 2016.Concluded there are significant practice backhand groundstrokes drive using Modified Two On One and methods Rhythm Drill in men's tennis player Phapros Clubs Year 2016. The modified method of two-on-one better. Tennis coach in order to make creative training methods in order ateltnya not get bored..